Nursing students’ perception of the quality of clinical learning: a mixed methods inquiry - La Sala, Rachele; Ruozi, Corrado; Gavagni, Santina; Martelli, Michele; Marletta, Giuseppe; Primosa, Flavia (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: As part of the Nursing Degree Course, the “internship” period represents a strategic lever to systemize the fundamental combination of theoretical study and nursing practice. However, only a few studies have examined in depth students’ perception of this experience. The aim of the study was to assess the quality of the places in which the University of Parma’s Nursing students did their internships based on their experience. Methods: Through a quantitative and qualitative study, students who had completed at least one clinical internship (n.200) were asked to fill out a self-report questionnaire on the quality of learning using the CLEQUEI scale (1) and answer a few social and demographical questions. In addition to the questionnaire, 24 narrative interviews (semi-structured) were conducted; these interviews deepened the significance of the assigned internship experience. Results: Throughout all the clinical contexts that were analyzed, the dimension of the perceived quality of the internship averaged a value ≥ 44 (the minimum cut-off indicating the presence of necessary elements to promote the processes of quality clinical learning). The perceived quality dimension particularly stands out in the Pediatric Area, in which it amounted to a mean value of 66 (close to the maximum cut-off value of > 66). This result indicates the opportunity to further develop the processes used in students’ quality clinical learning. The latter describe the internship as a moment of both personal and professional growth of fundamental importance in one’s own training process. Conclusions: Overall, the University of Parma’s Nursing students have a good perception of the quality of clinical learning. The significance of assigned internship presents some elements which are a relevant part of the new paradigm. However, there are still some aspects which need improvement, such as the necessity to reevaluate certain parts of the teaching organization of the professionalizing activities and of the clinical internships throughout the duration of the three-year course.